Comparison of pharmacy technicians’ and doctors’ medication transcribing errors at hospital discharge - Lloyd, Michael (Eur J Hosp Pharm, 2020)
OBJECTIVES: To compare the transcribing error rates of discharge prescriptions between pharmacy technicians and doctors in an acute hospital setting. METHODS: Pharmacy technicians were trained in the transcribing of discharge medications from inpatient to discharge medication charts. Prospective prescribing audits were undertaken over 5 days on eight hospital medical wards by ward pharmacists to compare pharmacy technician (on four wards) and doctor (on four wards) discharge transcribing error rates. Transcribed discharge medications were compared with the inpatient medication list by ward pharmacists to identify any transcription errors. Transcribing data for each technician and doctor, and number of items and errors, were input into SPSS and analysed using relevant statistical tests. RESULTS: Doctors (n=12) transcribed 77 discharge prescriptions, and 678 items with 127 errors recorded (18.7% error rate). Pharmacy technicians (n=8) transcribed 63 discharge prescriptions, and 654 items with 25 errors recorded (3.8% error rate), a significant difference between groups in error frequency (χ(2)(1)=58.6, p=<0.005) with a 14.9% difference between groups. CONCLUSIONS: Pharmacy technicians have significantly lower discharge transcribing error rates compared with doctors. This service intervention has the potential to improve patient safety and minimise inefficiencies from correcting errors. Further work is needed to explore the views and opinions of service users of the intervention, and why technician-transcribing error rates are significantly lower than doctors.